Causes and management of aggression and violence in a forensic mental health service: Perspectives of nurses and patients. (21st November 2012) - Dickens, Geoffrey; Piccirillo, Maria; Alderman, Nick
Abstract: Nurses' attitudes about the causes and management of aggression affects their choice of intervention. We aimed to compare the attitudes held by patients and staff in a forensic mental health service with the Management of Aggression and Violence Attitudes Scale, and examine the factor validity of the tool in this setting by conducting a prospective comparative questionnaire survey. Staff ( n = 72) and patient ( n = 98) attitudes differed to a limited extent. Confirmatory factor analysis refuted the previously reported structure of the tool. Exploratory factor analysis suggested three underlying factors related to modifiability of aggression, hands on management, and hands off management. Patients were more optimistic than nurses about the modifiability of aggressive behaviour. Male patients and those with diagnoses other than personality disorder were significantly more likely to agree about modifiability than controls. Forensic inpatients recognize the need for the use of a range of techniques to prevent and manage aggression and violence, but selected groups are most likely to believe that aggression is modifiable. Prevention and management of aggression training should emphasize the modifiability of aggressive behaviour. The development of measures of modifiability and management style would assist in the evaluation of training and would offer new avenues for research.